Kajian Pemanfaatan Sumberdaya Pangan Lokal Terhadap Ketahanan Pangan Rumah Tangga (Studi kasus: Desa Kolam, Percut Sei Tuan, Kab. Deli Serdang) - Bakara, Siska Gabriela; Saleh, Khairul (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
This study aims to analyze the level of household food security and the contribution of local food resources in meeting food needs in Kolam Village, Percut Sei Tuan District, Deli Serdang Regency. The research employed a quantitative descriptive method through surveys and interviews with household respondents. The results show that household food security in Kolam Village is relatively low, with 58% of households categorized as food insecure and only 42% as food secure. The utilization of local food sources, such as corn, cassava, and sweet potatoes, remains very limited, contributing only 5% and 2%, respectively, which falls under the very low category. In contrast, rice remains the dominant staple food, contributing 91%, indicating a high dependency on this commodity. These findings highlight the need to enhance local food-based diversification efforts to strengthen household food security and reduce dependence on rice.